Patient Satisfaction of Outpatient Services of a Level 1 Private Hospital in Western Visayas, Philippines - Sheryl S. Divinagracia; Joseph G. Guevarra (Philippine Social Science Journal, 2025)
This quantitative descriptive-comparative study evaluated patient satisfaction with Outpatient Department (OPD) services at a level 1 private hospital, specifically assessing doctors, nurses, access, appointments, and facilities. Utilizing a modified Grogan et al. (2000) questionnaire on 385 adult respondents selected via quota and convenience sampling, the research found general satisfaction with medical personnel and accessibility, but distinct dissatisfaction with hospital facilities. Statistical analysis revealed that while factors like age and sex did not impact results, family monthly income was a significant differentiator, suggesting socioeconomic disparities in perceived care quality. Consequently, the study recommends that administrators prioritize facility upgrades and equitable resource allocation to address these income-based gaps. Future research should expand generalizability through longitudinal, mixed-methods studies across multiple institutions to further explore the nuances of patient experience.